Apple consumption reduces markers of postprandial inflammation following a high fat meal in overweight and obese adults: A randomized, crossover trial. Issue 14 (8th June 2021) - Liddle, Danyelle M.; Lin, Xinjie; Ward, Emily M.; Cox, Liam C.; Wright, Amanda J.; Robinson, Lindsay E.
Abstract : Whole apples in combination with a high fat meal mitigated plasma and peripheral blood mononuclear cell markers of postprandial inflammation in individuals with overweight and obesity. Abstract : High fat meal-induced postprandial inflammation is exacerbated in overweight and obesity and may contribute to cardiovascular disease (CVD) risk. This study aimed to determine the effects of apples, rich in anti-inflammatory polyphenols, on biomarkers of postprandial inflammation in individuals with overweight and obesity. A randomized, crossover trial was conducted with n = 26 participants (17 female/9 male; mean age 45.5 ± 3.12 years; mean BMI 34.1 ± 1.18 kg m −2 ) to assess the effects of 3 whole Gala apples (∼200 g) on the 2, 4 and 6 h postprandial response to a high fat meal providing 1 g fat per kg body weight. Changes in plasma biomarkers of inflammation (as the primary outcome) and endotoxin exposure, non-esterified fatty acids (NEFA) and total antioxidant capacity (TAC) were measured. Fasting (0 h) and 4 h peripheral blood mononuclear cells (PBMC) were also isolated from whole blood and stimulated with or without a physiological dose (10 ng mL −1 ) of lipopolysaccharide (LPS) to measure secreted cytokines. Apples modulated postprandial plasma IFN-γ and reduced its peak concentration (−12.8%), and increased both 4 h (14.4%) and peak (10.5%) TAC ( P < 0.05). In unstimulated and LPS-stimulated PBMC, apples reduced secreted IL-6 (−49.3% and −17.1%) and TNF-α (−43.3% and −14.7%) and increased IL-4 (93.1% and 15.8%) in both the unstimulated and LPS-stimulated conditions, as well as decreased GM-CSF (−26.0%) and IL-17 (−47.9%) in unstimulated PBMC and G-CSF (−19.8%) in LPS-stimulated PBMC ( P < 0.05). These data suggest acute whole Gala apple consumption may be an effective dietary strategy to mitigate high fat meal-induced postprandial inflammation that exacerbates CVD risk in overweight and obesity. This study was registered at clinicaltrials.gov, NCT03523403, The Apple Study: Investigating the Effects of Whole Apple Consumption on Risk Factors for Chronic Metabolic Diseases in Overweight and Obese Adults.